O40-2 National prevalence of occupational exposure to asthmagens. (1st September 2016) - Fritschi, Lin; Crewe, Julie; Darcey, Ellie; Reid, Alison; Glass, Deborah; Benke, Geza; Driscoll, Tim; Peters, Susan; Si, Si; Abramson, Michael; Carey, Renee
Abstract : For effective occupational health improvement programs, it is important to understand the distribution of exposures on a national scale. With regards to occupational asthma, such information is most useful when it relates to specific asthmagens rather than general classifications such as "vapours, gas, dust or fumes". We aimed to provide this information for Australia by conducting a national telephone survey of the prevalence of current occupational exposure to 277 asthmagens, classified into 27 groups. We telephoned a sample of mobile and landline numbers to seek participation. Eligible participants aged 18 to 64 years and currently working were asked basic demographic and job questions. A web-based application, OccIDEAS, was used to collect job-specific information about tasks done and to automatically assign exposure to one or more asthmagen groups based on this information. In our sample of 4878 participants (2441 men and 2437 women), exposure to at least one asthmagen was more common among men (47%) than women (40%). The most common exposures in men were bioaerosols (29%) and metals (27%), and in women were latex (25%) and industrial cleaning and sterilising agents (20%). We extrapolated these findings to the Australian working population, and estimate that 2.8 million men and 1.7 million women are exposed to at least one asthmagen in their current job, representing 55% and 37% of the workforce respectively. Our findings about the prevalence of occupational exposure to specific asthmagens in Australia will be useful in setting priorities for the control of exposures and prevention of occupational asthma.